A predictive hybrid force modeling in turning: application to stainless steel dry machining with a coated groove tool. Issue 1 (July 2015) - Czarnota, Christophe; Koné, Fousseny; Haddag, Badis; Nouari, Mohammed
Abstract This paper presents an hybrid numerical/analytical modeling for estimation of cutting forces in machining process. The approach dedicated to predict 3D cutting forces are based on a chip flow direction modeling coupled with plane strain numerical simulations. An equivalent uncut chip thickness, deduced from the chip flow direction, is used as an input parameter in the 2D FEM. Resulting 2D numerical cutting forces are thus obtained from FEM, and knowing the chip flow direction, tangential, radial, and feed forces are calculated. Cutting forces derived from the proposed approach are compared to experiments when machining 304L austenitic steel with a groove-coated tool under dry condition. To take into account the complex groove geometry, the real shape of the cutting tool used in experiments has been captured by means of a digitization procedure, and thus implemented in 2D plane strain numerical simulations. The approach is applied to the case of stainless steel turning over a great range of cutting conditions. Two chip flow direction modelings are considered for the cutting force decomposition where it is shown the good predictive capabilities of the proposed approach.